Placenta Pathologies in Two Patients With Glycogen Storage Disease Type Ia and Preeclampsia - V. Laufs; A. Hasenburg; M. A. Busch; F. Lang; D. Macchiella; E. Mildenberger; L. Seidmann; J. B. Hennermann (JIMD Reports, 2025)
ABSTRACT Little is known about pregnancies and placental changes in women with glycogen storage disease type Ia (GSD Ia). We report on two primipara with GSD Ia who both developed preeclampsia and whose newborns were small for gestational age. Both placentas showed sonomorphological and macroscopical abnormalities. Disease‐specific histological features could not be identified, which should prompt further research.